TNF-α-induced Inflammation Stimulates Apolipoprotein-A4 via Activation of TNFR2 and NF-κB Signaling in Kidney Tubular Cells - Hyung Ho Lee (Nature Portfolio, 2017)
Abstract Apo-A4 expression was increased in tissues from chronic kidney disease (CKD) patients compared to that in normal kidney tissue. We determined the association of apo-A4 and its regulatory signals following acute kidney injury and elucidated the effects of apo-A4 on cell signaling pathways related to kidney injury in vitro and in vivo. Tumor necrosis factor (TNF)-α, which causes inflammatory cell injury, induced significantly increased expression of apo-A4 protein levels, and these levels were related to pro-inflammatory acute kidney injury in human kidney cells. Apo-A4 expression was also increased in experimented rat kidney tissues after ischemic reperfusion injury. The expression of tumor necrosis factor receptor (TNFR) 2 was increased in both kidney cell lines and experimented rat kidney tissues following acute kidney injury. The expression of apo-A4 and TNFR2 was increased upon treatment with TNF-α. Immunohistochemistry revealed positive apo-A4 and TNFR2 staining in ischemic reperfusion injury rat kidneys compared with levels in the sham operation kidneys. After neutralization of TNF-α, NF-κB expression was only observed in the cytoplasm by immunofluorescence. Therefore, the apo-A4 expression is increased by stimulation of injured kidney cells with TNF-α and that these effects occur via a TNFR2-NFκB complex.